Unveiling interdisciplinary horizons: students’ experiences in a first-year calculus course - Armenta, Itzel H.; Dominguez, Angeles (Frontiers in Education, 2024)
In the realm of higher education, the pursuit of interdisciplinarity aims to foster the exchange and integration of fragmented knowledge, yielding transformative outcomes. This study delves into the heart of this endeavor, engaging twelve students from a first-year undergraduate calculus class. Employing Moustakas (1994) phenomenological method, we aim to grasp the essential nature of their interdisciplinary experience within the course. Through the analysis of written questionnaires, focus group sessions, and supplementary qualitative data, a comprehensive understanding of students' interdisciplinary encounters is unveiled. This paper presents emergent experiential themes, shedding light on both individual and collective experiences, as students navigate and enrich their calculus learning through interdisciplinary connections.